Natural Resource Exploitation and the Legal Struggles of Indigenous Communities - Ilhafa, Fayza; Arrizal, Nizam Zakka; Gyasi, Jennis Benewaa (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2025)
The exploitation of natural resources in Indonesia often leads to conflicts between indigenous communities and government or private entities. This article examines the role of law in protecting the rights of indigenous peoples concerning the utilization of natural resources within their territories. Employing a normative legal research method based on secondary legal materials. The findings reveal that, although the rights of indigenous peoples are constitutionally recognized, as stipulated in Articles 18B(2) and 28I(3) of the 1945 Constitution of the Republic of Indonesia, their practical implementation remains inadequate. A significant challenge lies in the conflict between customary law and state law, particularly in the management of natural resources. Indigenous communities frequently face barriers in accessing and utilizing their resources due to regulatory frameworks that often disregard their interests. This article highlights the urgent need for harmonization between customary and state laws and emphasizes the importance of strengthening institutional capacities to support sustainable natural resource management. Preventive and repressive legal protections are essential to ensure that the rights of indigenous communities are not only formally acknowledged but also effectively safeguarded and implemented. By integrating UNDRIP principles into the national legal framework, Indonesia can promote social justice and environmental sustainability, ensuring that indigenous rights are respected and protected.